Ceolita Na-P desarrollada a partir de montmorillonita, incorporada en morteros - Marfil, Silvina Andrea (1994)
A zeolite Na-P crystallized from the montmorillonite incorporated with the aggregates in mortar bars was found. The montmorillonite was used to study mineralogic changes in an environment where the alkali-silica reaction can take place. The product developed was study by means of XRD, optical microscopy and SEM.